Technology and techniques in automotive film production - Maltcev, Ilia; Truhlář, Filip; Krist, Antonín; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
In this work I review technologies which are used in automotive films, such as carcommercials or action chase scenes. In the theoretical part I describe different camerasystems and platforms as well as their placement and movement for producing dynamicshots that emotionally impact audience. Additionally, I introduce a brief historical evolution ofsuch systems. Furthermore, I examine vehicle coordination and various driving techniquesthat improve visual imagery. These findings are applied in the practical part, where I producea demo reel which contains my own car shots.
Vedoucí práce: Filip Truhlář
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses